Hemodynamic effects of intraoperative 30% versus 80% oxygen concentrations: an exploratory analysis - Reiterer, Christian; Fleischmann, Edith; Kabon, Barbara; Taschner, Alexander; Kurz, Andrea; Adamowitsch, Nikolas; von Sonnenburg, Markus Falkner; Fraunschiel, Melanie; Graf, Alexandra (Frontiers in Medicine, 2023)
Background Supplemental oxygen leads to an increase in peripheral vascular resistance which finally increases systemic blood pressure in healthy subjects and patients with coronary artery disease, heart failure, undergoing heart surgery, and with sepsis. However, it is unknown whether this effect can also be observed in anesthetized patients having surgery. Thus, we evaluated in this exploratory analysis of a randomized controlled trial the effect of 80% versus 30% oxygen on intraoperative blood pressure and heart rate. Methods We present data from a previous study including 258 patients, who were randomized to a perioperative inspiratory FiO2 of 0.8 (128 patients) versus 0.3 (130 patients) for major abdominal surgery. Continuous arterial blood pressure values were recorded every three seconds and were exported from the electronic anesthesia record system. We calculated time-weighted average (TWA) and Average Real Variability (ARV) of mean arterial blood pressure and of heart rate. Results There was no significant difference in TWA of mean arterial pressure between the 80% (80 mmHg [76, 85]) and 30% (81 mmHg [77, 86]) oxygen group (effect estimate −0.16 mmHg, CI –1.83 to 1.51; p = 0.85). There was also no significant difference in TWA of heart rate between the 80 and 30% oxygen group (median TWA of heart rate in the 80% oxygen group: 65 beats.min−1 [58, 72], and in the 30% oxygen group: 64 beats.min−1 [58; 70]; effect estimate: 0.12 beats.min−1, CI –2.55 to 2.8, p = 0.94). Also for ARV values, no significant differences between groups could be detected. Conclusion In contrast to previous results, we did not observe a significant increase in blood pressure or a significant decrease in heart rate in patients, who received 80% oxygen as compared to patients, who received 30% oxygen during surgery and for the first two postoperative hours. Thus, hemodynamic effects of supplemental oxygen might play a negligible role in anesthetized patients. Clinical Trail Registration https://clinicaltrials.gov/ct2/show/NCT03366857?term=vienna&cond=oxygen&draw=2&rank=1